The influence of competence, job placement, and workload on employee performance through intrinsic motivation as an intervening variable in the communication and informatics department of the Riau Islands Provincial Government - Firmansyah, Donny; Satriawan, Bambang; Indrawan, Mohammad Gita (Goodwood Publishing, 2024)
Purpose: This study investigates the effects of competence, job placement, and workload on employee performance, with intrinsic motivation serving as an intervening variable. The context is the Communication and Informatics Department of the Riau Islands Provincial Government, where digital transformation demands strong human resource management. Research Methodology: The study applied a quantitative approach using Partial Least Squares (PLS) analysis with SmartPLS 4.0. Data were collected from 105 employees, representing the full population of the department. Constructs such as competence, job placement, workload, intrinsic motivation, and performance were measured through validated Likert-scale questionnaires. Results: The analysis indicates that competence, job placement, and workload significantly affect employee performance both directly and indirectly through intrinsic motivation. Intrinsic motivation serves as a mediating factor, strengthening the relationship between human resource variables and performance outcomes. Conclusions: The findings underscore the importance of aligning employee competence with job placement, distributing workload effectively, and fostering intrinsic motivation to achieve optimal performance. For government institutions undergoing digital transformation, supportive leadership and recognition practices are critical to enhancing service delivery and organizational effectiveness. Limitations: The research is limited to one government agency, which restricts generalization to broader contexts. The cross-sectional design captures relationships at one point in time, limiting insights into long-term dynamics. Moreover, other potential factors influencing performance, such as organizational culture or leadership style, were not included. Contribution: Research contributes to public sector HRM by evidencing how competence, placement, workload, and motivation interact in digital transformation.